Analisis Kebangkrutan dengan Model Altman Z-Score pada Perusahaan Sektor Industri Dasar dan Kimia di Bei Periode 2013-2014 - Suci Kurniawati (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
The purpose of this study is to analyze the company's financial distress on basis industry and chemical sectors as many as 57 companies using the ALTMAN Z-Score model in 2013-2014. The data which used was secondary data, such as Financial Statements of manufacturing company publication issued by Indonesian Stock Exchange (BEI) and obtained by downloading the website: www.idx.com. This study uses descriptive quantitative method. The finding of Z-Score index in basis industry and chemical sector in 2013 is occupied by PT. Intan Wijaya Internasional Tbk on chemical subsector and 2014 is occupied by PT. Alakasa Industrindo Tbk on metal subsector and others, with the first highest rank and healthy condition, whereas the last and lowest rank on wood and processing sector in 2013-2014 is PT. SLJ Global Tbk, with having financial distress condition. The findings of this study are not consistent or even in accordance with the reality which shows that the Altman method can not be used as a tool to indicate a tendency towards company’s financial distress.